PKM DAP (Drilling Amiyah Program) berbasis Karakter KBIHU JBAL Nur Sidoarjo - Hikmah, Khizanatul; Amrullah, Muhlasin; Ammar, Farikh Marzuqi; Iqbal, Waritsuddin Ibnu; Habibi, Wipa Raziq Sihab (Universitas Nusantara PGRI Kediri, 2024)
Drilling Amiyah Character-based program is a program to support social interaction in everyday life using Amiyah Arabic by integrating Islamic values. The partner in the community service program is KBIHU Jabal Nur Sidoarjo with 120 participants. The results of interviews and observations resulted in two partner problems, namely related to 1) the lack of teaching staff (HR) both in terms of qualifications and Arabic language competencies, 2) the unavailability of Amiyah Arabic conversation guides. And the solutions provided by the community service team are 1) mentoring and training in the form of Drilling Amiyah Practice, 2) Compilation of practical Amiyah Arabic language guides. While the results of the community service are as follows 1) There is an increase in the movement of KBIHU Jabal Nur hajj and umrah pilgrims in communicative Amiyah Arabic language skills. 2) the availability of a Character-Based Amiyah Practice Arabic Language guidebook for KBIHU Jabal Nur hajj and umrah pilgrims as a reference and guide in communicating.